IMPROVING STUDENTS’ MOTIVATION AND SPEAKING COMPETENCE BY USING THINK-PAIR-SHARE STRATEGY - Ahmad Hanan; Hera Aulia Budiarti (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2019)
This research was aimed at describing whether or not Think-Pair-Share strategy is able to improve the students’ motivation and speaking competence. The research was a Classroom Action Research. The data collected through qualitative and quantitative ways. The instruments used by the researcher were speaking test, observation sheet and questionnaire. The finding of the research showed that the strategy can improve the students’ motivation and speaking competence. The improvement can be seen from the result of note taking and observation sheet. In cycle one there were 20 out of 30 students improved their motivation which was also supported by questionnaire result of 84%. In cycle two the result of note taking and observation sheet showed that there were 25 out of 30 students improved their motivation which was also supported by questionnaire result of 91%. The mean score of the students also showed an improvement, from 63, 53 on first cycle to 84 on the second cycle. So, it could be concluded that using Think-Pair-Share strategy was able to improve the students’ motivation and speaking competence.